Catalytic dust removal filter material and preparation method thereof

By designing catalytic dust removal filters, using the combined technology of needle-punching and polymer microporous membranes, the problem of difficulty in removing particulate matter and harmful gases at the same time in the prior art is solved, and efficient catalytic purification and structural stability are achieved.

CN119869240APending Publication Date: 2025-04-25NANJING FIBERGLASS RES & DESIGN INST CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411986256.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Existing industrial dust collectors are difficult to efficiently capture particulate matter and remove harmful gases accompanied by emissions, such as nitrogen oxides and dioxins, and the catalyst is unevenly distributed, easy to fall off, and the catalytic efficiency is low.

Method used

A catalytic dust removal filter is designed, which consists of a first adhesive layer, a catalytic layer, a second adhesive layer and a filter layer arranged in sequence. The catalytic layer is prepared by a fiber web supported by a catalyst and acupuncture method to ensure uniform distribution of the catalyst and long-term stability.

Benefits of technology

It realizes efficient catalytic decomposition of harmful gases such as nitrogen oxides and dioxins during the dust removal process, improves catalytic purification efficiency, extends the service life of the filter material, and enhances structural stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119869240A_ABST
    Figure CN119869240A_ABST
Patent Text Reader

Abstract

The invention relates to a catalytic dust removal filter material and a preparation method thereof. The catalytic dust removal filter material sequentially comprises a first binder layer, a catalytic layer, a second binder layer and a filter layer, the first binder layer and the second binder layer are prepared by adopting a foaming process; the catalyst layer is obtained by needling a fiber net loaded with a catalyst; and the filter layer is a polymer microporous membrane. The catalytic dust removal filter material prepared by the invention not only can efficiently capture particulate matters, but also can catalytically decompose harmful gases such as nitrogen oxides in the dust removal process, and is particularly suitable for industrial dust removers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of industrial dust removal, and in particular to a catalytic dust removal filter material and a preparation method thereof. Background Art

[0002] Traditional industrial dust collectors mainly focus on the capture of particulate matter, but have not effectively treated harmful gases such as nitrogen oxides and dioxins that are emitted along with particulate matter. With increasingly stringent environmental protection requirements, the development of composite filter materials that can remove both particulate matter and harmful gases has become an urgent need in the industry. Although there are filter materials on the market that can purify harmful gases by adding catalysts, there are still problems such as uneven catalyst distribution, easy detachment, and low catalytic efficiency, and the overall structure and performance of the filter material still need to be optimized. Summary of the invention

[0003] The present invention provides a catalytic dust removal filter material and a preparation method thereof. The catalytic dust removal filter material can not only efficiently capture particulate matter, but also catalytically decompose harmful gases such as nitrogen oxides and dioxins during the dust removal process, and is particularly suitable for use in industrial dust collectors.

[0004] In the first aspect, the present invention provides a catalytic dust removal filter material, which comprises in sequence: a first binder layer, a catalytic layer, a second binder layer and a filter layer; the first binder layer and the second binder layer are both prepared by a foaming process; the catalytic layer is obtained by needle-punching a fiber mesh loaded with a catalyst; and the filter layer is a polymer microporous membrane.

[0005] Preferably, the pore size of the first adhesive layer is 10 μm to 150 μm.

[0006] Preferably, the first adhesive layer is prepared from a fluorine-containing polymer, a foaming agent and a foam stabilizer through a foaming process.

[0007] More preferably, the mass ratio of the fluorine-containing polymer, the blowing agent and the foam stabilizer is 1:(0.05-0.25):(0.05-0.25).

[0008] Preferably, the fiber used in the fiber web is at least one of inorganic fiber and organic fiber.

[0009] More preferably, the diameter of the inorganic fiber is 3 μm to 13 μm, and the fineness of the organic fiber is 0.5 to 8 denier.

[0010] Preferably, the catalyst is at least one of a manganese-based catalyst, a vanadium-based catalyst, and an iron-based catalyst.

[0011] More preferably, the manganese-based catalyst is at least one of a manganese oxide catalyst, a manganese-based composite catalyst, and a manganese nanocatalyst; the vanadium-based catalyst is at least one of a vanadium-titanium catalyst, a vanadium-tungsten catalyst, and a vanadium phosphoric acid catalyst; and the iron-based catalyst is at least one of ferric chloride and iron (III) trifluoromethanesulfonate.

[0012] More preferably, the particle size of the catalyst is less than 100 mesh.

[0013] Preferably, the catalyst layer is a catalyst-loaded needle-punched felt obtained by needle-punching a fiber mesh loaded with catalyst; the surface density of the needle-punched felt is 500 to 1000 g / m 2 ; The content of the catalyst is 3wt% to 30wt% of the needle-punched felt.

[0014] Preferably, the porosity of the catalytic layer is 60% to 85%.

[0015] More preferably, the porosity of the catalytic layer is 70% to 80%.

[0016] Preferably, the catalytic layer is obtained by needle punching multiple layers of fiber webs, and the content of the catalyst carried by each layer of the fiber web is different.

[0017] More preferably, the catalytic layer is obtained by sequentially stacking a first fiber web and a second fiber web carrying the catalyst and punching them; wherein, in the direction from the filter layer to the first adhesive layer, the catalyst content carried by the first fiber web gradually decreases.

[0018] More preferably, the catalytic layer is obtained by needling a first fiber web carrying the catalyst, a second fiber web, and a third fiber web carrying the catalyst; wherein the content of the catalyst loaded on the first fiber web facing the second adhesive layer is higher than the content of the catalyst loaded on the third fiber web facing the first adhesive layer.

[0019] Preferably, the pore size of the second adhesive layer is 10 μm to 150 μm.

[0020] Preferably, the second adhesive layer is prepared from fluorine-containing polymer, acrylic emulsion, foaming agent and foam stabilizer through a foaming process.

[0021] More preferably, the mass ratio of the fluorine-containing polymer, the acrylic emulsion, the foaming agent and the foam stabilizer is 1:1:(0.05-0.25):(0.05-0.25).

[0022] Preferably, the fluorine-containing polymer is polytetrafluoroethylene or ethylene-tetrafluoroethylene copolymer;

[0023] The foaming agent is sodium lauryl sulfate;

[0024] The foam stabilizer is hydroxyethyl cellulose.

[0025] Preferably, the average pore size of the polymer microporous membrane is less than 2 μm and the porosity is not less than 70%.

[0026] Preferably, the polymer microporous membrane is a polytetrafluoroethylene microporous membrane, an ethylene-tetrafluoroethylene copolymer microporous membrane, a polypropylene microporous membrane or a polyethylene microporous membrane.

[0027] In a second aspect, the present invention further provides a method for preparing the catalytic dust removal filter material of the first aspect, comprising:

[0028] (1) spreading a catalyst on a fiber web, and then needle-punching the fiber web loaded with the catalyst to obtain a catalytic layer;

[0029] (2) coating the first adhesive layer and the second adhesive layer obtained by the foaming process on the upper surface and the lower surface of the catalyst layer respectively;

[0030] (3) Bonding the filter layer to the side of the second binder layer facing away from the catalytic layer to obtain the catalytic dust removal filter material.

[0031] Preferably, the fluorine-containing polymer, the foaming agent and the foam stabilizer are mixed and foamed to obtain the first adhesive layer;

[0032] The fluorine-containing polymer, acrylic emulsion, foaming agent and foam stabilizer are mixed and foamed to obtain the second adhesive layer.

[0033] Compared with the prior art, the present invention has at least the following beneficial effects:

[0034] The catalytic dust removal filter material provided by the present invention comprises a first binder layer, a catalytic layer, a second binder layer and a filter layer arranged in sequence. The filter layer serves as a dust-facing surface. Waste gas containing particulate matter and harmful gases passes through the filter layer, the second binder layer, the catalytic layer and the first binder layer in sequence. While efficiently capturing particulate matter, the catalytic layer can also be used to catalytically decompose harmful gases such as nitrogen oxides and dioxins during the dust removal process. The filter material is suitable for use in industrial dust collectors.

[0035] The present invention ensures the uniform distribution and long-term stability of the catalyst in the catalytic dust removal filter material through the precisely controlled catalyst spreading and fixing technology, effectively improves the catalytic decomposition efficiency of harmful gases such as nitrogen oxides, and realizes efficient catalytic purification.

[0036] The present invention adopts the design of needle punching and shaping combined with polymer microporous membrane, which not only enhances the physical strength of the catalytic dust removal filter material, but also effectively prevents the catalyst from falling off from the catalytic layer, enhances the structural stability of the catalytic dust removal filter material, and prolongs the service life of the catalytic dust removal filter material.

[0037] The polymer microporous membrane used in the present invention has excellent filtering efficiency and air permeability, and can efficiently capture ultrafine particles; and while ensuring the fixation of the catalyst, it can also ensure the free diffusion of gas molecules, ensuring the smooth progress of the dust removal and catalytic purification process. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0039] Figure 1 A schematic diagram of the structure of a catalytic dust removal filter material provided in one embodiment of the present invention;

[0040] Figure 2 A schematic diagram of the structure of a catalyst layer provided by one embodiment of the present invention;

[0041] Figure 3 A SEM image of a catalyst layer provided in one embodiment of the present invention;

[0042] Reference numerals: 10 - first adhesive layer; 20 - catalytic layer; 30 - second adhesive layer; 40 - filtration layer; 201 - first fiber web; 202 - second fiber web; 203 - third fiber web. DETAILED DESCRIPTION

[0043] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0044] like Figure 1As shown, an embodiment of the present invention provides a catalytic dust removal filter material, which includes: a first binder layer 10, a catalytic layer 20, a second binder layer 30 and a filter layer 40 in sequence; the first binder layer 10 and the second binder layer 30 are both prepared by a foaming process; the catalytic layer 20 is obtained by needle-punching a fiber mesh loaded with a catalyst; and the filter layer 40 is a polymer microporous membrane.

[0045] In an embodiment of the present invention, the catalytic dust removal filter material includes a first binder layer, a catalytic layer, a second binder layer and a filter layer arranged in sequence. The filter layer serves as the dust-facing surface. The exhaust gas containing particulate matter and harmful gases passes through the filter layer, the second binder layer, the catalytic layer and the first binder layer in sequence. While efficiently capturing particulate matter, the catalytic layer can also be used to catalytically decompose harmful gases such as nitrogen oxides during the dust removal process, and is suitable for use in industrial dust collectors. At the same time, the catalytic layer is obtained by acupuncture of a fiber mesh loaded with a catalyst, which ensures the uniform distribution and long-term stability of the catalyst in the catalytic dust removal filter material, effectively improves the catalytic decomposition efficiency of harmful gases such as nitrogen oxides, and achieves efficient catalytic purification.

[0046] It should be noted that in the present invention, the thickness of each layer, such as the first binder layer, the catalytic layer, the second binder layer and the filter layer, is designed according to actual application requirements.

[0047] In some preferred embodiments, the pore size of the first adhesive layer is 10 μm to 150 μm (for example, it can be 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm or 150 μm).

[0048] In the present invention, in order to ensure that the first adhesive layer can effectively prevent the catalyst from falling, provide exposure of the catalytic active area for the catalyst layer, and provide good air permeability to reduce gas phase mass transfer resistance, the pore size of the first adhesive layer is selected to be 10 μm to 150 μm. It should be noted that the porosity of the first adhesive layer can ensure the good air permeability provided, and preferably the porosity of the first adhesive layer is 70% to 85% (for example, it can be 70%, 75%, 80% or 85%).

[0049] In some preferred embodiments, the first adhesive layer is prepared from a fluorine-containing polymer, a foaming agent, and a foam stabilizer through a foaming process.

[0050] In some more preferred embodiments, the mass ratio of the fluorinated polymer, the blowing agent and the foam stabilizer is 1:(0.05-0.25):(0.05-0.25) (for example, it can be 1:0.05:0.05, 1:0.05:0.1, 1:0.05:0.15, 1:0.05:0.2, 1:0.05:0.25, 1:0.1:0.05, 1:0.15:0.05, 1:0.2:0.05, 1:0.25:0.05, 1:0.25:0.25).

[0051] In the present invention, a high-porosity structure is formed by a foaming process using a fluorine-containing polymer, a foaming agent and a foam stabilizer, and the pore size is 10μm to 150μm. This not only makes the first adhesive layer have excellent adhesion and can be firmly combined with the catalyst layer to improve the stability of the overall structure of the catalytic dust removal filter material, but also can provide additional air permeability and exposure of the catalyst active sites, and prevent the catalyst from falling from its pores.

[0052] Since sulfate has a moderate hydrophilic-lipophilic balance (HLB value) and a small steric hindrance, sodium dodecyl sulfate has good water solubility and the ability to migrate to the gas-liquid interface, and can form a relatively close arrangement at the gas-liquid interface, so it has a good foaming ability at a low concentration. In the present invention, it has been experimentally confirmed that if the amount of foaming agent is too much, the foaming speed of the system is too fast, a large number of virtual bubbles and large bubbles with poor stability are generated, and bubble breaking is easy to occur under subsequent conditions; if the amount of foaming agent is too little, it directly affects the foaming ability of the fluorine-containing polymer, and the foaming speed is too slow. If the amount of foam stabilizer is too high, an overly dense arrangement will be formed in the bubble wall membrane, the amount of liquid in the formed foam will be reduced, the brittleness of the surface film will increase, and the foam will be more unstable; if the amount of foam stabilizer is too low, it will not only lead to a slowdown in the foaming process, extend the production cycle, but also fail to effectively form a protective film on the bubble surface, resulting in a decrease in foam stability and easy rupture. Therefore, the mass ratio of the fluorine-containing polymer, the blowing agent and the foam stabilizer is limited to 1:(0.05~0.25):(0.05~0.25).

[0053] Specifically, the fluorine-containing polymer is polytetrafluoroethylene or ethylene-tetrafluoroethylene copolymer; the foaming agent is sodium lauryl sulfate; and the foam stabilizer is hydroxyethyl cellulose.

[0054] In some preferred embodiments, the catalyst is at least one of a manganese-based catalyst, a vanadium-based catalyst, and an iron-based catalyst.

[0055] In some more preferred embodiments, the manganese-based catalyst is at least one of a manganese oxide catalyst, a manganese-based composite catalyst, and a manganese nanocatalyst; the vanadium-based catalyst is at least one of a vanadium-titanium catalyst, a vanadium-tungsten catalyst, and a vanadium phosphoric acid catalyst; and the iron-based catalyst is at least one of ferric chloride and iron (III) trifluoromethanesulfonate.

[0056] In some more preferred embodiments, the particle size of the catalyst is less than 100 mesh (for example, it can be 99 mesh, 95 mesh, 90 mesh, 85 mesh, 80 mesh, 75 mesh, 70 mesh, 65 mesh, 60 mesh, 55 mesh, 50 mesh, 45 mesh, 40 mesh, 30 mesh, etc.).

[0057] In the present invention, a catalyst with a particle size of less than 100 mesh is selected, which has a large surface area and many active sites, and can more effectively promote the catalytic reaction, while avoiding the problem that its particle size is too unfavorable for the dispersion and adhesion of the catalyst, and also avoiding the problem that the catalyst particle size is too small and easy to agglomerate. However, it should be noted that in order to prevent the catalyst from falling from the first adhesive layer and the second adhesive layer, the particle size of the catalyst is preferably larger than the pore size of the first adhesive layer and the second adhesive layer.

[0058] In some preferred embodiments, the fibers used in the fiber web are at least one of inorganic fibers and organic fibers.

[0059] It should be noted that at least one is any one or a mixture of any several in any proportion.

[0060] In some more preferred embodiments, the diameter of the inorganic fiber is 3μm to 13μm (for example, it can be 3μm, 3.5μm, 4μm, 4.5μm, 5μm, 5.5μm, 6μm, 6.5μm, 7μm, 7.5μm, 8μm, 8.5μm, 9μm, 9.5μm, 10μm, 10.5μm, 11μm, 11.5μm, 12μm, 12.5μm or 13μm), and the fineness of the organic fiber is 0.5 to 8 denier (for example, it can be 0.5 denier, 1 denier, 1.5 denier, 2 denier, 2.5 denier, 3 denier, 3.5 denier, 4 denier, 4.5 denier, 5 denier, 5.5 denier, 6 denier, 6.5 denier, 7 denier, 7.5 denier or 8 denier).

[0061] In some preferred embodiments, the catalyst layer is a catalyst-loaded needle-punched felt obtained by needle-punching a fiber web loaded with catalyst; the surface density of the needle-punched felt is 500 to 1000 g / m 2 (For example, it can be 500g / m 2 , 550g / m 2 , 600g / m 2 , 650g / m 2 , 700g / m 2 , 750g / m 2 , 800g / m 2 , 850g / m 2 , 900g / m 2 , 950g / m 2 or 1000g / m 2); the content of the catalyst is 3wt% to 30wt% of the needle felt (for example, it can be 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt%, 5.5wt%, 6wt%, 6.5wt%, 7wt%, 8wt%, 9wt%, 10wt%, 12wt%, 15wt%, 18wt%, 20wt%, 22wt%, 25wt%, 28wt% or 30wt%).

[0062] In the present invention, it has been experimentally confirmed that if the amount of catalyst is less than 3wt%, the catalytic efficiency of the prepared catalytic dust removal filter material is low; if the amount of catalyst is more than 30wt%, the air permeability of the catalyst layer is seriously affected, thereby affecting the purification efficiency of the catalytic dust removal filter material. At the same time, while limiting the amount of catalyst, the diameter or fineness of the fiber and the surface density of the needle-punched felt are further limited, so that the prepared needle-punched felt can provide more attachment sites and loading areas for the catalyst, and can have suitable pores, good air permeability and can capture part of the particulate matter, and can also make the catalyst more evenly distributed in the pores and surface to avoid the catalyst from agglomerating or falling off.

[0063] In some preferred embodiments, the porosity of the catalytic layer is 60% to 85% (e.g., 60%, 62%, 65%, 68%, 70%, 72%, 75%, 78%, 80%, 82% or 85%).

[0064] In the present invention, in order to provide good air permeability to reduce gas phase mass transfer resistance, improve catalytic dust removal efficiency, and allow harmful gases to fully contact the catalyst in the catalytic layer, the porosity of the catalytic layer is limited to 60% to 85%.

[0065] In some more preferred embodiments, the porosity of the catalytic layer is 70% to 80% (for example, it may be 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79% or 80%).

[0066] In some more preferred embodiments, the catalytic layer is obtained by needle punching multiple layers of fiber webs, and the content of catalyst carried by each layer of fiber web is different.

[0067] In the present invention, the catalyst layer can be obtained by needle punching a single fiber mesh or a multi-layer fiber mesh. For the catalyst layer obtained by needle punching a multi-layer fiber mesh, the content of the catalyst carried by each fiber mesh layer can be designed according to the actual application requirements, and the content of the catalyst carried by each fiber mesh layer does not exceed 30wt% of the layer.

[0068] In some more preferred embodiments, the catalytic layer is obtained by sequentially stacking a first fiber web and a second fiber web loaded with catalyst and punching them; wherein the catalyst content loaded on the first fiber web gradually decreases in the direction from the filter layer to the first adhesive layer.

[0069] Specifically, for example, the catalytic layer can be obtained by stacking a first fiber mesh loaded with catalyst and a second fiber mesh in two layers and by needling, or by stacking a first fiber mesh loaded with catalyst, a second fiber mesh, and a first fiber mesh loaded with catalyst in three layers and by needling, or by stacking a first fiber mesh loaded with catalyst, a second fiber mesh, a first fiber mesh loaded with catalyst, and a second fiber mesh in four layers and by needling. Specifically, the catalyst content loaded on the first fiber mesh is the mass fraction of the catalyst in the weight of the first fiber mesh, and the difference in the catalyst content loaded on adjacent first fiber meshes is 5wt% to 10wt% (for example, it can be 5wt%, 5.5wt%, 6wt%, 6.5wt%, 7wt%, 7.5wt%, 8wt%, 8.5wt%, 9wt%, 9.5wt% or 10wt%). It should be noted that the direction from the filter layer to the first adhesive layer is the exhaust gas transmission direction.

[0070] In an embodiment of the present invention, a first fiber mesh loaded with a catalyst and a second fiber mesh are stacked in sequence, and the catalyst content loaded on the first fiber mesh gradually decreases along the exhaust gas transmission direction. This allows the exhaust gas passing through the filter layer to first pass through the first fiber mesh with the highest catalyst content to achieve preliminary removal of harmful gases and remove some particulate matter and pollutants, and can also pass through the second fiber mesh to further remove particulate matter, dust and other suspended matter in the exhaust gas. At the same time, the exhaust gas with reduced harmful gas content continues to pass through the first fiber mesh with gradually reduced catalyst content and the second fiber mesh without catalyst load in sequence, which can achieve multiple fine filtrations, ensure that the harmful gas fully reacts with the catalyst, make the exhaust gas more and more pure in subsequent treatment, remove harmful gases in the exhaust gas to the maximum extent, and improve the treatment efficiency of the catalytic layer.

[0071] In some more preferred embodiments, Figure 2 The catalytic layer shown is obtained by needling a first fiber web 201 loaded with catalyst, a second fiber web 202, and a third fiber web 203 loaded with catalyst; wherein the content of catalyst loaded on the first fiber web 201 facing the second adhesive layer is higher than the content of catalyst loaded on the third fiber web 203 facing the first adhesive layer.

[0072] In an embodiment of the present invention, after passing through the filter layer, the exhaust gas first passes through a first fiber mesh with a high catalyst content to achieve preliminary removal of harmful gases and remove some particulate matter and pollutants; then it passes through a second fiber mesh to further remove particulate matter, dust and other suspended matter in the exhaust gas; then it passes through a third fiber mesh with a low catalyst content to achieve removal of residual harmful gases and residual pollutants, thereby maximally removing harmful substances in the exhaust gas and improving the processing efficiency of the catalytic layer.

[0073] In some preferred embodiments, the pore size of the second adhesive layer is 10 μm to 150 μm (for example, it can be 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm or 150 μm).

[0074] In some preferred embodiments, the second adhesive layer is prepared from fluorine-containing polymer, acrylic emulsion, foaming agent and foam stabilizer through a foaming process.

[0075] In some more preferred embodiments, the mass ratio of the fluorinated polymer, acrylic emulsion, blowing agent and foam stabilizer is 1:1:(0.05-0.25):(0.05-0.25) (for example, it can be 1:1:0.05:0.05, 1:1:0.05:0.1, 1:1:0.05:0.15, 1:1:0.05:0.2, 1:1:0.05:0.25, 1:1:0.1:0.05, 1:1:0.15:0.05, 1:1:0.2:0.05, 1:1:0.25:0.05, 1:1:0.25:0.25).

[0076] In the present invention, the second adhesive layer has two functions: one is to firmly bond the catalytic layer and the filter layer to improve the overall structural stability of the catalytic dust removal filter material; the second is to effectively prevent the catalyst from falling, and provide the catalytic layer with exposure of the catalytic active area, providing good air permeability. Therefore, the pore size of the second adhesive layer is selected to be 10μm to 150μm, and acrylic emulsion is added during the preparation process to further improve the bonding performance and temperature resistance. Since the second adhesive layer is closer to the dust-facing surface than the first adhesive layer, it is required to have higher temperature resistance. The temperature range of the second adhesive layer is 260℃ to 330℃, and the temperature range of the first adhesive is 100℃. It should be noted that the porosity of the second adhesive layer can ensure the good air permeability provided, and preferably the porosity of the first adhesive layer is 70% to 85% (for example, it can be 70%, 75%, 80% or 85%).

[0077] Specifically, the fluorine-containing polymer is polytetrafluoroethylene or ethylene-tetrafluoroethylene copolymer; the foaming agent is sodium lauryl sulfate; and the foam stabilizer is hydroxyethyl cellulose.

[0078] In some preferred embodiments, the average pore size of the polymer microporous membrane is less than 2 μm (for example, it may be 1.9 μm, 1.8 μm, 1.7 μm, 1.6 μm, 1.5 μm, 1.2 μm, 1.0 μm, 0.9 μm, 0.8 μm, 0.6 μm, 0.5 μm, 0.3 μm, 0.2 μm, etc.), and the porosity is not less than 70% (for example, it may be 70%, 72%, 75%, 78%, 80%, 82% or 85%, etc.).

[0079] In some preferred embodiments, the polymer microporous membrane is a polytetrafluoroethylene microporous membrane, an ethylene-tetrafluoroethylene copolymer microporous membrane, a polypropylene microporous membrane or a polyethylene microporous membrane.

[0080] The present invention also provides a method for preparing the above-mentioned catalytic dust removal filter material, comprising:

[0081] (1) Spreading a catalyst on a fiber web, and then needle-punching the fiber web loaded with the catalyst to obtain a catalytic layer;

[0082] (2) coating the first adhesive layer and the second adhesive layer obtained by the foaming process on the upper surface and the lower surface of the catalyst layer respectively;

[0083] (3) The filter layer is bonded to the side of the second adhesive layer facing away from the catalytic layer to obtain a catalytic dust removal filter material.

[0084] Specifically, in step (1), spreading the catalyst on the fiber web includes: placing the fiber web on a conveyor belt, and evenly spreading the catalyst treated with a particle size less than 100 mesh, and ensuring that the catalyst is evenly distributed on the fiber web by controlling the speed and amount of spreading the catalyst and the speed of the conveyor belt.

[0085] Specifically, needle punching and catalyst fixing: the fiber net sprinkled with the catalyst is put into the needle punching machine, and the bonding force between the fibers is enhanced by the needle punching process to form a stable composite needle punched felt (i.e., the catalyst layer). During the needle punching process, a small amount of catalyst will be punctured out of the surface. Therefore, the present invention adds a layer of polymer microporous membrane as a filter layer through a second adhesive layer on the side of the composite needle punched felt that is susceptible to wear or the catalyst is easy to fall off. The porous structure of the filter layer is designed to have a pore size smaller than the catalyst particle size, which can effectively lock the catalyst and prevent it from falling off, while maintaining a certain air permeability and exposure of the catalytic active area.

[0086] The present invention ensures uniform distribution and long-term stability of the catalyst in the catalytic dust removal filter material through precisely controlled catalyst spreading and fixing technology, effectively improves the catalytic decomposition efficiency of harmful gases such as nitrogen oxides, and realizes efficient catalytic purification. At the same time, the catalytic dust removal filter material can be obtained by bonding with the first adhesive layer and the second adhesive layer, and no heat setting treatment is required. Therefore, the preparation method of the catalytic dust removal filter material of the present invention is simpler and easier to operate, and can significantly improve the production efficiency of the catalytic dust removal filter material.

[0087] In some preferred embodiments, the fluorine-containing polymer, the foaming agent and the foam stabilizer are mixed and foamed to obtain the first adhesive layer;

[0088] The fluorine-containing polymer, acrylic emulsion, foaming agent and foam stabilizer are mixed and foamed to obtain the second adhesive layer.

[0089] It should be noted that the foaming treatment of the first adhesive layer and the second adhesive layer is performed at room temperature.

[0090] In the present invention, unless otherwise specified, the raw materials used may be products that can be directly purchased on the market or synthesized by existing methods. In the present invention, "and / or" between multiple technical features indicates that these technical features are connected in an "and / or" relationship, indicating that it may be any one of these technical features, or a combination of any two or more of these technical features.

[0091] The present invention will be further described below by way of examples, but the protection scope of the present invention is not limited to these embodiments.

[0092] Example 1

[0093] like Figure 1 As shown, the catalytic dust removal filter material includes, from top to bottom, a first binder layer 10 with a thickness of 0.1 mm, a catalyst layer 20 with a thickness of 4 mm, a second binder 30 with a thickness of 0.2 mm, and a filter layer 40 with a thickness of 10 μm; wherein the filter layer 40 is the dust-facing surface;

[0094] The first adhesive layer 10 is obtained by foaming polytetrafluoroethylene PTFE, a foaming agent (sodium lauryl sulfate) and a foam stabilizer (hydroxyethyl cellulose) at a mass ratio of 1:0.25:0.25 at room temperature, and has a pore size of less than 150 μm and a porosity of 75%;

[0095] The catalyst is composed of vanadium pentoxide V2O5, tungsten trioxide WO3, and titanium dioxide TiO2 in a mass ratio of 3:1:96, and the catalyst particle size is less than 150μm; the fiber mesh includes a reinforcing fiber cloth and a felt layer, and the reinforcing fiber cloth is composed of glass fiber with a fineness of 6μm and a surface density of 350g / m 2 The felt layer is made of glass fiber (diameter 6 μm, length 6 cm) with a fiber weight fraction of 80% and polyimide PI fiber (2.2 denier) with a fiber weight fraction of 20% by carding and needle punching process.

[0096] Preparation of the catalytic layer 20: Evenly spread the catalyst on the fiber web, the catalyst content is 20wt% of the fiber web, and then the fiber web spread with the catalyst enters the needle punching machine, and obtains the catalyst-loaded needle felt, i.e., the catalytic layer, through the needle punching process; wherein the needle punching density is 200-400 needles / cm 2 , the needle punching depth is 5 to 15 mm and the stepping amount is 4 mm / needle; the surface density of the needle punched felt is 800 g / m 2 The porosity of the catalytic layer is 75%;

[0097] The second adhesive layer 30 is obtained by foaming polytetrafluoroethylene PTFE, acrylic emulsion, foaming agent (sodium lauryl sulfate) and foam stabilizer (hydroxyethyl cellulose) at a mass ratio of 1:1:0.25:0.25 at room temperature, and has a pore size of less than 150 μm and a porosity of 85%;

[0098] The filter layer 40 is a polymer microporous membrane made of polyethylene with an average pore size of less than 2 μm and a porosity of 50%;

[0099] Preparation of catalytic dust removal filter material: the foam obtained by foaming for preparing the first binder layer is coated on the upper surface of the catalytic layer to obtain a catalytic layer bonded with the first binder layer; the foam obtained by foaming for preparing the second binder layer is coated on the lower surface of the catalytic layer to obtain a catalytic layer bonded with the first binder layer and the second binder layer; and the filter layer is bonded to the side of the second binder layer away from the catalytic layer to obtain a catalytic dust removal filter material.

[0100] The catalyst layer prepared in Example 1 was characterized by electron microscopy, and the following results were obtained: Figure 3 The SEM images shown are Figure 3 It can be seen that the catalyst is evenly distributed on the fibers.

[0101] Example 2

[0102] Example 2 is basically the same as Example 1, except that the catalytic layer is different.

[0103] like Figure 2As shown, the catalyst layer is obtained by needle punching a first fiber mesh 201 loaded with catalyst, a second fiber mesh 202, and a third fiber mesh 203 loaded with catalyst; wherein the content of the catalyst loaded on the first fiber mesh 201 facing the second binder layer is 25wt%; the content of the catalyst loaded on the third fiber mesh 203 facing the first binder layer is 15wt%;

[0104] The first fiber web 201 with a thickness of 1.5 mm is made of polyimide PI fiber with a fineness of 2.2 denier and a surface density of 150 g / m 2 ;

[0105] The second fiber mesh 202 with a thickness of 1 mm does not carry a catalyst and is a glass fiber base cloth. The diameter of the glass fiber is 6 μm and the surface density is 380 g / m 2 ;

[0106] The third fiber mesh 203 with a thickness of 1.5 mm is made of glass fiber with a diameter of 6 μm and a surface density of 400 g / m 2 ;

[0107] Preparation of the catalytic layer 20: The catalyst is evenly spread on the first fiber web and the third fiber web respectively, and then the first fiber web 201, the second fiber web 202 and the third fiber web 203 spread with the catalyst are stacked in sequence and put into the needle punching machine together, and the catalyst-loaded needle felt, i.e., the catalytic layer, is obtained by the needle punching process; wherein the needle punching density is 200-400 thorns / cm 2 , the needle penetration depth is 5 to 15 mm and the stepping amount is 4 mm / needle; the porosity of the catalytic layer is 80%.

[0108] Example 3

[0109] Example 3 is basically the same as Example 1, except that the catalyst content in the catalytic layer is 3wt% of the fiber web.

[0110] Example 4

[0111] Example 4 is basically the same as Example 1, except that the catalyst content in the catalytic layer is 30wt% of the fiber web.

[0112] Example 5

[0113] Example 5 is basically the same as Example 1, except that the porosity of the catalyst layer is 60%, and the surface density of the needle felt of the catalyst layer is 800 g / m 2 , thickness is 3.20mm.

[0114] Example 6

[0115] Example 6 is basically the same as Example 1, except that the porosity of the catalyst layer is 85%, and the surface density of the needle felt of the catalyst layer is 800 g / m 2 , thickness is 4.53mm.

[0116] Example 7

[0117] like Figure 1 As shown, the catalytic dust removal filter material includes, from top to bottom, a first binder layer 10 with a thickness of 0.05 mm, a catalyst layer 20 with a thickness of 2.0 mm, a second binder 30 with a thickness of 0.1 mm, and a filter layer 40 with a thickness of 15 μm; wherein the filter layer 40 is the dust-facing surface;

[0118] The first adhesive layer 10 is obtained by foaming polytetrafluoroethylene PTFE, a foaming agent (sodium lauryl sulfate) and a foam stabilizer (hydroxyethyl cellulose) at a mass ratio of 1:0.10:0.10 at room temperature, and has a pore size of less than 150 μm and a porosity of 70%;

[0119] The catalyst is composed of vanadium pentoxide V2O5, tungsten trioxide WO3, and titanium dioxide TiO2 in a mass ratio of 1:1:98, and the catalyst particle size is less than 150μm; the fiber mesh includes a reinforcing fiber cloth and a felt layer, and the reinforcing fiber cloth is composed of glass fiber with a fineness of 6μm and a surface density of 300g / m 2 The felt layer is made of glass fiber (diameter 7 μm, length 5 cm) with a fiber weight fraction of 70% and aramid fiber (2.2 denier) with a fiber weight fraction of 30% by carding and needle punching process;

[0120] Preparation of the catalytic layer 20: Spread the catalyst evenly on the fiber web, then put the fiber web with the catalyst into a needle punching machine, and obtain a needle punched felt loaded with the catalyst, i.e., the catalytic layer, by a needle punching process; wherein the needle punching density is 200 to 400 needles / cm 2 , the needle punching depth is 5 to 15 mm and the stepping amount is 4 mm / needle; the surface density of the needle punched felt is 750 g / m 2 The porosity of the catalyst layer is ?%; the catalyst dosage is 95g / m 2 , i.e. the catalyst content is 95 / 750=12.6wt% of the fiber web;

[0121] The second adhesive layer 30 is obtained by foaming polytetrafluoroethylene PTFE, acrylic emulsion, foaming agent (sodium lauryl sulfate) and foam stabilizer (hydroxyethyl cellulose) at a mass ratio of 1:1:0.10:0.10 at room temperature, and has a pore size of less than 150 μm and a porosity of 70%;

[0122] The filter layer 40 is a polymer microporous membrane made of polytetrafluoroethylene with an average pore size of less than 2 μm and a porosity of 85%;

[0123] Preparation of catalytic dust removal filter material: the foam obtained by foaming for preparing the first binder layer is coated on the upper surface of the catalytic layer to obtain a catalytic layer bonded with the first binder layer; the foam obtained by foaming for preparing the second binder layer is coated on the lower surface of the catalytic layer to obtain a catalytic layer bonded with the first binder layer and the second binder layer; and the filter layer is bonded to the side of the second binder layer away from the catalytic layer to obtain a catalytic dust removal filter material.

[0124] Example 8

[0125] Example 8 is basically the same as Example 7, except that the surface density of the needle felt is 750 g / m 2 The catalyst dosage is 120g / m 2 , that is, the catalyst content is 120 / 750=16wt%.

[0126] Example 9

[0127] Example 9 is basically the same as Example 7, except that the surface density of the needle felt is 750 g / m 2 The catalyst dosage is 130g / m 2 , that is, the catalyst content is 130 / 750=17.3wt%.

[0128] Example 10

[0129] Example 10 is basically the same as Example 7, except that the surface density of the needle felt is 750 g / m 2 The catalyst dosage is 180g / m 2 , that is, the catalyst content is 180 / 750=24wt%.

[0130] Embodiment 11

[0131] Example 11 is basically the same as Example 1, except that the first adhesive layer is different.

[0132] Specifically, the first adhesive layer 10 is obtained by foaming polytetrafluoroethylene PTFE, a foaming agent (sodium lauryl sulfate) and a foam stabilizer (hydroxyethyl cellulose) in a mass ratio of 1:0.05:0.05, and has a pore size of less than 150 μm and a porosity of 85%.

[0133] Example 12

[0134] Example 12 is basically the same as Example 1, except that the second adhesive layer is different.

[0135] Specifically, the second adhesive layer 30 is obtained by foaming polytetrafluoroethylene PTFE, acrylic emulsion, foaming agent (sodium lauryl sulfate) and foam stabilizer (hydroxyethyl cellulose) in a mass ratio of 1:1:0.05:0.05, and has a pore size of less than 150 μm and a porosity of 85%.

[0136] Comparative Example 1

[0137] Comparative Example 1 is substantially the same as Example 1, except that the catalyst layer is not formed using a needle punching process.

[0138] Specifically, the preparation of the catalytic layer 20 is as follows: the catalyst is evenly spread on the fiber web, and the catalyst content is 20wt% of the fiber web to obtain the catalytic layer.

[0139] Comparative Example 2

[0140] Comparative Example 2 is substantially the same as Example 1, except that the first adhesive layer is replaced by the first layer, and the second adhesive layer is replaced by the second layer.

[0141] Specifically, the first layer is a polytetrafluoroethylene porous membrane layer with a thickness of 0.1 mm, a pore size of less than 150 μm, and a porosity of 70%; the second layer is a polytetrafluoroethylene porous membrane layer with a thickness of 0.2 mm, a pore size of less than 150 μm, and a porosity of 75%;

[0142] Preparation of catalytic dust removal filter material: After the catalytic layer and the second layer are treated with a treatment liquid containing 1%wt coupling agent KH550, 20%SF-1PTFE emulsion, 9% acrylic acid and 70% water and treated in an oven at 200°C, the upper surface of the catalytic layer is laminated to the first layer, the lower surface of the catalytic layer is laminated to the second layer, and the filter layer is laminated to the other side of the second layer at 340°C, a pressure of 0.2MPa, and a speed of 12m / min to form a catalytic dust removal filter material.

[0143] Comparative Example 3

[0144] Comparative Example 3 is substantially the same as Example 1, except that the second adhesive layer is different.

[0145] Specifically, the second adhesive layer 30 is obtained by foaming polytetrafluoroethylene PTFE, acrylic emulsion, foaming agent (sodium lauryl sulfate) and foam stabilizer (hydroxyethyl cellulose) in a mass ratio of 1:1:0.01:0.01 at room temperature, and has a pore size of less than 200 μm and a porosity of 60%.

[0146] Comparative Example 4

[0147] Comparative Example 4 is substantially the same as Example 1, except that the second adhesive layer is different.

[0148] Specifically, the second adhesive layer 30 is obtained by foaming polytetrafluoroethylene PTFE, a foaming agent (sodium lauryl sulfate) and a foam stabilizer (hydroxyethyl cellulose) in a mass ratio of 1:0.25:0.25 at room temperature, with a pore size of less than 150 μm and a porosity of 75%.

[0149] The catalytic dust removal filter materials prepared in the above examples and comparative examples were used as samples to conduct catalytic dust removal tests, and the test results shown in Table 1 were obtained.

[0150] The experimental device of the test method consists of a gas distribution device, a flow meter, a mixing tank, a preheater, a reactor for setting the sample (i.e., the catalytic filter) and a monitoring system. x The conversion rate test was carried out in this experimental device, and the sample diameter was 150mm. Test conditions: The simulated exhaust gas composition was NH35×10 -4 、NO 5×10 -4 、SO22×10 -4 , O25%, H2O 5% and N2 are used as carrier gases, and the reaction temperature is 175-250°C. After the reaction gases are fully mixed in the mixing tank, they are preheated in the preheater and finally enter the reactor. The gasmet analyzer is used as the monitoring system to continuously monitor the composition and content of the reactor inlet and outlet gases online.

[0151] Table 1

[0152]

[0153] As can be seen from Table 1, compared with Example 1, Example 2 has a catalytic layer obtained by needle punching multiple layers of fiber mesh, and the content of the catalyst loaded on each layer of fiber mesh is different, so the catalytic decomposition effect of nitrides is better, and the removal rate is higher than that of Example 1. At the same time, compared with Example 1, Example 4 has a higher content of catalyst used in the catalytic layer, so Example 4 has a better catalytic decomposition effect of nitrides than Example 1. Compared with Example 1, Comparative Example 1 directly spreads the catalyst on the fiber mesh without needle punching, and the catalyst is not fixed and easy to fall off, so the removal rate of nitrides is lower than that of Example 1. Comparative Example 2 uses an impregnation method to achieve interlayer bonding, and does not use a foamed adhesive layer, so its interlayer bonding is poor, and it also requires high-temperature heat setting treatment to obtain a catalytic dust removal filter material, and the preparation process is relatively complicated. In Comparative Example 3, due to the low amount of foaming agent and foam stabilizer used, the foam formation speed is slow during the foaming process, it is difficult to effectively form a protective film on the bubble surface, the bubble is easy to rupture, and the pore size of the second adhesive layer is large after rupture, and the catalyst is easy to fall off, so the removal rate of nitride is low. In Comparative Example 4, the second adhesive layer does not use acrylic emulsion, because its temperature resistance at 250°C is poor, thus affecting the removal rate of nitride.

[0154] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them; although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the above embodiments, or replace some of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present invention. The parts not described in detail in the present invention are well-known technologies of those skilled in the art.

Claims

1. A catalytic dust removal filter material, characterized in that: Including in order: A first adhesive layer, a catalytic layer, a second adhesive layer and a filter layer; the first adhesive layer and the second adhesive layer are both prepared by a foaming process; The catalytic layer is obtained by needle-punching a fiber mesh loaded with catalyst; and the filter layer is a polymer microporous membrane.

2. The catalytic dust removal filter material according to claim 1, characterized in that: The pore size of the first adhesive layer is 10 μm to 150 μm; and / or, The first adhesive layer is prepared from a fluorine-containing polymer, a foaming agent and a foam stabilizer through a foaming process; preferably, the mass ratio of the fluorine-containing polymer, the foaming agent and the foam stabilizer is 1:(0.05-0.25):(0.05-0.25).

3. The catalytic dust removal filter material according to claim 1, characterized in that: The fiber web is made of at least one of inorganic fiber and organic fiber; preferably, the diameter of the inorganic fiber is 3 μm to 13 μm, and the fineness of the organic fiber is 0.5 to 8 denier; and / or, The catalyst is at least one of a manganese-based catalyst, a vanadium-based catalyst, and an iron-based catalyst; preferably, the manganese-based catalyst is at least one of a manganese oxide catalyst, a manganese-based composite catalyst, and a manganese nanocatalyst; the vanadium-based catalyst is at least one of a vanadium-titanium catalyst, a vanadium-tungsten catalyst, and a vanadium phosphoric acid catalyst; the iron-based catalyst is at least one of ferric chloride and iron (III) trifluoromethanesulfonate; preferably, the particle size of the catalyst is less than 100 mesh.

4. The catalytic dust removal filter material according to claim 1, characterized in that: The catalyst layer is a catalyst-loaded needle-punched felt obtained by needle-punching a fiber mesh loaded with catalyst; the surface density of the needle-punched felt is 500 to 1000 g / m 2 ; The content of the catalyst is 3wt% to 30wt% of the needle felt; and / or, The porosity of the catalytic layer is 60% to 85%, preferably 70% to 80%.

5. The catalytic dust removal filter material according to claim 4, characterized in that: The catalytic layer is obtained by needle punching multiple layers of fiber mesh, and the content of the catalyst carried by each layer of the fiber mesh is different; Preferably, the catalytic layer is obtained by stacking a first fiber mesh and a second fiber mesh carrying the catalyst in sequence and by needle punching; wherein, in the direction from the filter layer to the first binder layer, the catalyst content carried by the first fiber mesh gradually decreases; More preferably, the catalytic layer is obtained by needling a first fiber web carrying the catalyst, a second fiber web, and a third fiber web carrying the catalyst; wherein the content of the catalyst loaded on the first fiber web facing the second adhesive layer is higher than the content of the catalyst loaded on the third fiber web facing the first adhesive layer.

6. The catalytic dust removal filter material according to claim 1, characterized in that: The pore size of the second adhesive layer is 10 μm to 150 μm; and / or, The second adhesive layer is prepared from fluorine-containing polymer, acrylic emulsion, foaming agent and foam stabilizer through a foaming process; preferably, the mass ratio of fluorine-containing polymer, acrylic emulsion, foaming agent and foam stabilizer is 1:1:(0.05-0.25):(0.05-0.25).

7. The catalytic dust removal filter material according to claim 2 or 6, characterized in that: The fluorine-containing polymer is polytetrafluoroethylene or ethylene-tetrafluoroethylene copolymer; The foaming agent is sodium lauryl sulfate; The foam stabilizer is hydroxyethyl cellulose.

8. The catalytic dust removal filter material according to any one of claims 1 to 7, characterized in that: The average pore size of the polymer microporous membrane is less than 2 μm and the porosity is not less than 70%; and / or, The polymer microporous membrane is a polytetrafluoroethylene microporous membrane, an ethylene-tetrafluoroethylene copolymer microporous membrane, a polypropylene microporous membrane or a polyethylene microporous membrane.

9. A method for preparing a catalytic dust removal filter material according to any one of claims 1 to 8, characterized in that: The preparation method comprises: (1) spreading a catalyst on a fiber web, and then needle-punching the fiber web loaded with the catalyst to obtain a catalytic layer; (2) coating the first adhesive layer and the second adhesive layer obtained by the foaming process on the upper surface and the lower surface of the catalyst layer respectively; (3) Bonding the filter layer to the side of the second binder layer facing away from the catalytic layer to obtain the catalytic dust removal filter material.

10. The preparation method according to claim 9, characterized in that: include: The fluorine-containing polymer, the foaming agent and the foam stabilizer are mixed and foamed to obtain the first adhesive layer; The fluorine-containing polymer, acrylic emulsion, foaming agent and foam stabilizer are mixed and foamed to obtain the second adhesive layer.